The modernist nationalist movement of the 1920's and the performance of Villa-Lobos (Ágora Journal, 2024)
Considering initially his insertion in the Brazilian modernist movement of the 1920s – together with names such as those of literary authors such as Mário de Andrade, Oswald de Andrade and Graça Aranha – the article analyzes some of the boldest works of the Brazilian musician Heitor Villa-Lobos, from a compositional point of view, with special attention to the last choros (the symphonic choros) of his famous composition series Choros, besides other works such as the Noneto. The central objective is to show the radically innovative character of this phase of Villa-Lobos musical writing, which makes this Brazilian composer the greatest representative of the musical avant-garde in Brazilian artistic circles of the period.
Keywords: Villa-Lobos; Choros; Modernism; Week of 1922; Brazilian music.